2021
DOI: 10.1038/s41467-021-26050-z
|View full text |Cite
|
Sign up to set email alerts
|

Current and projected regional economic impacts of heatwaves in Europe

Abstract: Extreme heat undermines the working capacity of individuals, resulting in lower productivity, and thus economic output. Here we analyse the present and future economic damages due to reduced labour productivity caused by extreme heat in Europe. For the analysis of current impacts, we focused on heatwaves occurring in four recent anomalously hot years (2003, 2010, 2015, and 2018) and compared our findings to the historical period 1981–2010. In the selected years, the total estimated damages attributed to heatwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(54 citation statements)
references
References 67 publications
0
54
0
Order By: Relevance
“…
Heatwaves have set new temperature records over most of the world recently, posing severe threats to humans and the ecosystems (García-León et al, 2021;Perkins-Kirkpatrick & Lewis, 2020). For example, western Europe and Scandinavia experienced record-breaking temperatures in the summer of 2019, leading to almost 400 deaths in the Netherlands and 1,500 deaths in France (Watts et al, 2021).
…”
mentioning
confidence: 99%
“…
Heatwaves have set new temperature records over most of the world recently, posing severe threats to humans and the ecosystems (García-León et al, 2021;Perkins-Kirkpatrick & Lewis, 2020). For example, western Europe and Scandinavia experienced record-breaking temperatures in the summer of 2019, leading to almost 400 deaths in the Netherlands and 1,500 deaths in France (Watts et al, 2021).
…”
mentioning
confidence: 99%
“…Empirical research has shown that extreme temperatures reduce labor productivity (21), damage crops (22,23), and increase mortality (9), among other effects. Because this research is often sector or region specific (24)(25)(26), a theoretical and empirical gap still remains between the nonlinearities identified at the local and sectoral level and the global economic assessments required to evaluate differing climate policies. Several empirical climate-economy studies have quantified the global economic effects of changes in average temperature (27)(28)(29)(30)(31)(32) and temperature variability (33) in an attempt to close this gap.…”
Section: Introductionmentioning
confidence: 99%
“…So, short-term temperature decreases are expected to help economies’ situation the year they take place. Indeed, sudden heatwaves in Europe are found to decrease these countries’ GDP by about 0.3–0.5% (García-León et al 2021 ). The fact that the short-run temperature effect is harmful but the long-run one is positive could be explained by the ability of countries to adapt to disastrous situations in the short run to the long run (Alagidede et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%